What Prospects for the Brazilian Ethanol Sector?. (April 2017) - Mielnik, Otavio; Serigati, Felippe; Giner, Céline
Summary: Brazilian ethanol is derived from sugarcane and is mostly used domestically as a transportation fuel either pure or mixed with gasoline. Brazilians will fill their cars with pure ethanol when its pump price in energy equivalent is lower than the price of gasohol, the mandatory mixture of ethanol and gasoline. Over the last decade, Brazilian ethanol companies have used debt financing to meet the expected increase in domestic and international ethanol demand, which did not fully realise. With the current economic crisis, the ethanol sector, the second largest worldwide, is restructuring and seeking additional earning opportunities; co‐generation and valorisation of by‐products are likely to develop. Political commitments towards the ethanol sector through mandatory blending obligations or the fuel taxation system are strong. Domestic ethanol demand should thus remain sustained in the medium term. In addition, sugarcane‐based ethanol has the best GHG emission reduction profile of all biofuels available on a large scale. Advanced ethanol based on sugarcane derived biomass has the potential to perform even better; here Brazil has a major role to play in the future. However massive flows of investments are needed to develop competitive and innovative large‐scale advanced ethanol production facilities in the country. Abstract : Brazilian ethanol is derived from sugarcane and is mostly used domestically as a transportation fuel either pure or mixed with gasoline. Brazilians will fill their cars with pure ethanol when its pump price in energy equivalent is lower than the price of gasohol, the mandatory mixture of ethanol and gasoline. Over the last decade, Brazilian ethanol companies have used debt financing to meet the expected increase in domestic and international ethanol demand, which did not fully realise. With the current economic crisis, the ethanol sector, the second largest worldwide, is restructuring and seeking additional earning opportunities; co‐generation and valorisation of by‐products are likely to develop. Political commitments towards the ethanol sector through mandatory blending obligations or the fuel taxation system are strong.